PENGARUH KOMISARIS INDEPENDEN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ulfa Luthfia Nanda; Yeni Fitriani Somantri (Jurnal Riset Keuangan dan Akuntansi, 2021)
Earning Management is actions taken through the choice of accounting policies with the aim to fulfilling own interest or increasing the market value of company. The aim of this research is to analyze the influence of independent commissioners to the earning management in bank companies listed on Indonesia Stock Exchange. This research with quantitatitve method. Population of this research are bank companies listed on Indonesia Stock Exchange in 2016- 2018. This research uses purposive sampling method and analysis used linear regression. The result show that independent commissioners have no effect on earning management of bank companies listed on Indonesia Stock Exchange.  Keywords : earning management, independent commissioners